(3GdbhGYOs - (3eMeO Hf CMeO Hf Ydj GdGOQjSj GdMSfj, CHh YHO Gddg GdJdeSGfj,J (B771 (3g` s
(3ChdgG (B:s
(3bGYOI HJGQc eMd GdfLGSI Edi GdWgGQI s
(3BNQgG (B:s
(3heMd GdESJZaGQ MjK JNTi GdYbhHI s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B327s
Keywords: (3CUhd Gdabgs